Soft Computing and Industry 2002
DOI: 10.1007/978-1-4471-0123-9_53
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Algorithm Based on Cell Loss for Dynamic Routing in ATM Networks

Abstract: Abstract. New B-ISDN will have to ensure a high standard of quality of service measured as delay in the communications, guarantee of safety communications and of course no loss of information. Although the routing optimization problem has been previously dealt with in the bibliography, not many works have been presented according to the routing in ATM networks using cell loss as the overall criterion. Here a new model based on cell loss is presented for an ATM network with matrix switches and queues at the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The Tabu Search algorithm was compared to the Genetic Algorithm first described in Cortés et al (2002), whose pseudocode is shown in the appendix. The solutions provided by the MSwP algorithm are also presented, showing the improvement reached by the TS and GA heuristics respectively.…”
Section: Computational Resultsmentioning
confidence: 99%
“…The Tabu Search algorithm was compared to the Genetic Algorithm first described in Cortés et al (2002), whose pseudocode is shown in the appendix. The solutions provided by the MSwP algorithm are also presented, showing the improvement reached by the TS and GA heuristics respectively.…”
Section: Computational Resultsmentioning
confidence: 99%
“…A flow formulation is considered in the paper, instead of a required path formulation. The approach presented in the paper only considers the call scale, instead of considering also the cell scale and the burst scale as it is mandatory for real time routing algorithms and, then, the approach is less ambitious than the approach presented in Medova (1998), even Cortés et al (2002). We refer to these two papers for a deepen more about ATM network performance and also Tsybakow's papers, see e.g.…”
Section: Model's Simplificationsmentioning
confidence: 92%
“…1 shows a representation of the information flow at a terminal node and its relationship with the variables of the model. Cortés et al (2002) and Medova (1998) path oriented formulations. A potential drawback for this type of formulations can occur if the number of paths is big enough.…”
Section: Sets Smentioning
confidence: 99%
See 2 more Smart Citations